1991
DOI: 10.1044/jshr.3402.439
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Instrument to Measure Occupational Stress in Speech-Language Pathologists

Abstract: The Speech-Language Pathologist Stress Inventory (SLPSI) is a 48-item questionnaire adapted from the Teacher Stress Inventory (Fimian, 1988). Factor analyses of the responses of 626 speech-language pathologists revealed four stress source factors (Bureaucratic Restrictions, Time and Workload Management, Lack of Professional Supports, and Instructional Limitations) and two stress manifestation factors (Emotional-Fatigue Manifestations and Biobehavioral Manifestations). The internal consistency reliability of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 9 publications
0
33
1
Order By: Relevance
“…Such professionals have experienced the same tension, stress and negative attitudes others have encountered in the workplace. 76 Caseloads are large at 52 clients (range of 5-152), and 25% of SLPs report programme budgets under $100. The factors that lead to burnout include (a) bureaucratic restrictions (limit growth and effectiveness; little emotional and intellectual stimulation on the job); (b) emotional-fatigue manifestations (procrastination, call in sick, think of other things during conversations); (c) time and workload management (little time for preparation and personal priorities, over-commitment, excessive paperwork); (d) instructional limitations (students poorly motivated, do not improve and present discipline problems; inflexible scheduling); (e) biobehavioural manifestations (respiratory, cardiac, and gastrointestinal problems; use of drugs and alcohol) and (f) lack of professional supports (lack of recognition, alienated from school staff, misunderstood by public, lack of consultation opportunities).…”
Section: Speech-language Pathologistsmentioning
confidence: 99%
“…Such professionals have experienced the same tension, stress and negative attitudes others have encountered in the workplace. 76 Caseloads are large at 52 clients (range of 5-152), and 25% of SLPs report programme budgets under $100. The factors that lead to burnout include (a) bureaucratic restrictions (limit growth and effectiveness; little emotional and intellectual stimulation on the job); (b) emotional-fatigue manifestations (procrastination, call in sick, think of other things during conversations); (c) time and workload management (little time for preparation and personal priorities, over-commitment, excessive paperwork); (d) instructional limitations (students poorly motivated, do not improve and present discipline problems; inflexible scheduling); (e) biobehavioural manifestations (respiratory, cardiac, and gastrointestinal problems; use of drugs and alcohol) and (f) lack of professional supports (lack of recognition, alienated from school staff, misunderstood by public, lack of consultation opportunities).…”
Section: Speech-language Pathologistsmentioning
confidence: 99%
“…To this end, Fimian, Lieberman, and Fastenau (1991) Fimian et al (1991) identified one factor, Time and Workload Management, as the most significant contributor to stress, mirroring subsequent studies that identified workload, caseload, and time restraints as significant contributors to SLPs' stress level (Edgar & Rosa-Lugo, 2007).…”
mentioning
confidence: 73%
“…In discussing job satisfaction, schoolbased speech-language pathologists reported challenges that contribute to their perceived stress: lack of opportunities for professional development, decreased time, and diffi culty in workload management. 20 They also reported that additional stressors were related to scheduling and workload issues or limited effectiveness due to client characteristics that led to limited progress. The ICAP clinicians we interviewed felt that working in an ICAP reduced or eliminated those stressors to a certain degree.…”
Section: Challengesmentioning
confidence: 99%